2017
DOI: 10.1371/journal.pone.0183353
|View full text |Cite
|
Sign up to set email alerts
|

Pressure in isochoric systems containing aqueous solutions at subzero Centigrade temperatures

Abstract: ObjectivePreservation of biological materials at subzero Centigrade temperatures, cryopreservation, is important for the field of tissue engineering and organ transplantation. Our group is studying the use of isochoric (constant volume) systems of aqueous solution for cryopreservation. Previous studies measured the pressure-temperature relations in aqueous isochoric systems in the temperature range from 0°C to – 20°C. The goal of this study is to expand the pressure-temperature measurement beyond the range rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“… Phase diagram of water in temperature and pressure ranges relevant to the current study, as compiled from [ 11 ]. Also displayed are experimental results reported in the literature [ 12 ] and modeling results developed in the current study for similar conditions. …”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“… Phase diagram of water in temperature and pressure ranges relevant to the current study, as compiled from [ 11 ]. Also displayed are experimental results reported in the literature [ 12 ] and modeling results developed in the current study for similar conditions. …”
Section: Introductionmentioning
confidence: 81%
“…The proposed modeling approach is first validated in equilibrium conditions against classical literature data on pure water [ 11 ]. The proposed model is then compared with experimental results reported in the literature [ 12 ]. Finally, this study is used to provide insight into isochoric cooling and rewarming of pure water in a practical three-dimensional (3D) container.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly significant is the theoretical work by Szobota and Rubinsky [158], who showed that the probability for random ice nucleation decreases in an isochoric system; therefore, they predicted that the probability for vitrification will be enhanced in an isochoric system. Additionally, Ukpai et al [171] reported the thermodynamic profiles of solutions of Me 2 SO in pure water during cooling to and warming from cryogenic temperatures in an isochoric system. Subsequently, together with Rubinsky’s group, we showed that pressure measurement is important for designing and control of cryopreservation protocols in constant-volume (isochoric) systems and confirmed that any ice formation is associated with an increase in pressure, and that therefore pressure can be used as a measure for the occurrence of vitrification.…”
Section: Bioengineering Applicationsmentioning
confidence: 99%
“…Subsequently, together with Rubinsky’s group, we showed that pressure measurement is important for designing and control of cryopreservation protocols in constant-volume (isochoric) systems and confirmed that any ice formation is associated with an increase in pressure, and that therefore pressure can be used as a measure for the occurrence of vitrification. However, when ice is not formed, the pressure in the isochoric system does not increase during cooling, and in systems that vitrify, the absence of a pressure increase can confirm vitrification, observed pressure increases during a vitrification protocol can indicate devitrification, and temporal or static pressure measurements can be used as an objective substitute for or adjunct to more subjective visual inspection methods [28, 171, 172]. A comparison with results from the literature shows that the concentration of CPAs needed for vitrification in an isochoric chamber is substantially lower than that needed for vitrification in isobaric systems at 1 atm and in hyperbaric systems at 1,000 atm.…”
Section: Bioengineering Applicationsmentioning
confidence: 99%